Pengembangan Fiber Bragg Grating sebagai sensor temperatur dan tekanan berakurasi tinggi - Dedi Irawan; Azhar; Dodi Dahnus; Sara Rahmawati; Sutoyo (Jurnal Penelitian Pendidikan IPA, 2025)
The advancement of optical fiber technology has opened new opportunities in the development of high-accuracy sensors. This study focuses on the development of a Fiber Bragg Grating (FBG)-based sensor capable of simultaneously detecting temperature and pressure changes with high precision. FBGs are optical sensors that reflect specific wavelengths of light, which shift in response to external stimuli such as thermal expansion and mechanical strain. In this research, an FBG sensor system was designed, calibrated, and tested under controlled laboratory conditions to evaluate its sensitivity, linearity, and repeatability in detecting variations in temperature and pressure. The results show that the FBG sensor exhibits a high degree of accuracy and stability, with temperature sensitivity reaching up to 32 pm/°C and pressure sensitivity up to 32 pm/MPa. The dual-parameter sensing was achieved by using a configuration that separates the wavelength shifts induced by temperature and pressure through a compensation algorithm. This makes the proposed FBG sensor suitable for applications in harsh environments such as aerospace, biomedical, and industrial monitoring systems. The study concludes that FBG technology offers a promising platform for developing compact, reliable, and high-resolution sensing devices.